Information Technology Systems at the sharp end of medication therapy management. (November 2019) - Li, Reicelis Casares; Pereira, Rodrigo Arcuri Marques; Jatobá, Alessandro; Vidal, Mario Cesar Rodríguez; de Carvalho, Paulo Victor Rodrigues; Grindrod, Kelly; Burns, Catherine
This study explored how to inform the design of information systems for medication therapy management, in the context of the southwestern Ontario health system. The data collection comprised document analysis, interviews, and process mapping, and the analysis of previous interview records. The Functional Resonance Analysis Method (FRAM) was used for data analysis to identify the effects of functional variability in system outcomes, and to propose ways to redesign future systems. The results from the FRAM showed that shortcomings in the information systems require users to adapt in many ways. While these adjustments are essential to delivering care in everyday practice, they may lose their effectiveness in the face of specific situations, creating brittleness and risk of adverse outcomes as users are led to make challenging decisions.